On Diversity - Amy Cimini; Jairo Moreno (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
This article is part of a special forum titled “Ethnic Diversity in Music Theory: Voices from the Field.” Diversity has a relatively short but complex history inseparable from a vexing politics of cultural recognition in, and economic access to, American higher-education institutions. The authors consider this history along three interrelated axes—juridical, socio-political, and subjective—in order to discern the relation of cultural recognition and economic access to the ethos of the neoliberal university and to the structure of democratic institutions in late capitalism. The programmatic labor of the Society for Music Theory’s Committee on Diversity (1996–2007) provides the empirical backdrop for their discussion.